2020
DOI: 10.1016/j.biopha.2020.110678
|View full text |Cite
|
Sign up to set email alerts
|

ACE2, TMPRSS2 distribution and extrapulmonary organ injury in patients with COVID-19

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
189
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(201 citation statements)
references
References 186 publications
(334 reference statements)
1
189
0
11
Order By: Relevance
“…Transmembrane protease serine type2 (TMPRSS2), belonging to the type II transmembrane serine protease family, can cleave the coronavirus spike (S) protein and was demonstrated together with ACE2 to be crucial for the entry of SARS-CoV-2 into the host cells [ 17 , 18 ]. Recently, it has been found that ACE2 and TMPRSS2 are expressed not only in lung tissues, but also in extrapulmonary organs including heart, kidney, liver, colon, esophagus, brain, gallbladder and testis, suggesting that SARS-CoV-2 may also affect extrapulmonary organs [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Transmembrane protease serine type2 (TMPRSS2), belonging to the type II transmembrane serine protease family, can cleave the coronavirus spike (S) protein and was demonstrated together with ACE2 to be crucial for the entry of SARS-CoV-2 into the host cells [ 17 , 18 ]. Recently, it has been found that ACE2 and TMPRSS2 are expressed not only in lung tissues, but also in extrapulmonary organs including heart, kidney, liver, colon, esophagus, brain, gallbladder and testis, suggesting that SARS-CoV-2 may also affect extrapulmonary organs [19] .…”
Section: Introductionmentioning
confidence: 99%
“…The full-length cDNA encodes a predicted 492 amino acid protein, which is anchored to the plasma membrane and belongs to the TTSPs family (type II transmembrane serine proteases). In humans, TMPRSS2 is mainly expressed on prostate, pancreatic, and colon cells, but it can also be found in lung, liver, and kidney cells [17]. The entry of SARS-CoV-2 into host cells depends on the serine protease activity of TMPRSS283-87.…”
Section: Discussionmentioning
confidence: 99%
“…Since ACE2 is expressed in kidney cells, changes in the kidney due to COVID-19 need to have a point of focus [17]. Renal functioning needs to be monitored regularly, especially in patients with elevated plasma creatinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, about 20% patients developed viral infection from trachea to lungs [ 31 ]. SARS-CoV-2 binds with targets in alveolar epithelial cells such as ACE2 and TMPRSS2 and induces apoptosis response associated with vascular leakage [ 32 ]. This leakage causes the first wave of local inflammation and recruits immune cells from the blood into the lungs, thereby eliminating extracellular viruses and destroying infected cells [ 33 ].…”
Section: Role Of Tcm In Covid-19 Treatmentmentioning
confidence: 99%